Properties of a rapidly solidified Ni–Nb layer prepared using a high-current pulsed electron beam. (July 2020) - Sun, Pingping; Zhang, Conglin; Cai, Jie; Lyu, Peng; Jin, Yunxue; Guan, Qingfeng
Abstract: In this study, the surface of a bulk crystalline Ni–Nb powder metallurgy (PM) sample of a glass-forming composition was investigated using high-current pulsed electron-beam (HCPEB) irradiation, which also improved the surface properties. Unlike the original crystalline sample, X-ray diffraction (XRD) of the surface shows an amorphous phase following HCPEB exposure. Transmission electron microscopy (TEM) reveals that, after the Ni–Nb PM samples were exposed to 20 or 30 pulses of HCPEB irradiation, the re-melted layer contains localized nanocrystalline regions within an amorphous matrix. The scanning electron microscopy (SEM) results indicate that, after 30 pulses, a re-melted layer about 5 μm in thickness forms on the surface of the Ni–Nb PM samples. Meanwhile, a large number of cracks and craters were observed on the re-melted layer. In addition, the micro-hardness tests reveal that the micro-hardness improves significantly after HCPEB irradiation. The microhardness of the sample was the highest after the 30 pulses, which was 1.5 times that of the original sample. Furthermore, potentiodynamic polarization tests indicate that the irradiated samples of corrosion resistance were not enhanced compare to the initial samples, due to the formation of cracks providing a Cl − etching channel that accelerates the corrosion rate. Highlights: The Ni–Nb amorphous alloy layer was prepared by HCPEB irradiation. Amorphous and nanocrystalline were formed in the alloying layers. The surface composition of the alloys gradually becomes uniform. The microhardness and corrosion resistance were increased by HCPEB irradiation.